EFEKTIVITAS PELAKSANAAN PENGAWASAN DANA BOS (BANTUAN OPERASIONAL SEKOLAH) OLEH DINAS PENDIDIKAN - ", Andriyanto; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Bantuan operasional sekolah ( BOS ) is a government program for the provision of non- personnel operating costs of funds for basic education as the implementor of education program . According to Government Regulation No. 48 Year 2008 on Education Funding , non- personnel costs are costs for materials or educational equipment consumables , and indirect costs such as power , water , telecommunications services , maintenance of facilities and infrastructure , overtime , transportation , consumption , taxes and other therefore needed oversight in the implementation of the BOS program . In fact in the actual use of the funds by the school still found abuse of authority . The purpose of research was to investigate effectiveness the implementation of BOS funds supervision by the Department of Education Pekanbaru city and determine the factors that influence it. This research used a qualitative descriptive methods , data collection techniques with observation and interviewing the parties involved in monitoring the implementation of BOS funds as informants . This research uses Handoko theory , T Hani . The results indicate the supervision of BOS funds Elementary School in Pekanbaru has not worked effective overall despite the standards , goals and objectives clear , the number of supervisors indirect adequate , coordination and communication between members has been running well and the execution of tasks are in accordance with the applicable rules But the number of inspectors assigned directly is not adequate , because the number of supervisors is inversely proportional to the number of schools . Only a warning and a written warning and the enforcement of sanctions are not yet firm, resulting in blaming the authority in the use of the funds are not all resolved